Requirement Elicitation Modeling Using Knowledge Acquisition in Automated Specification Method - Hafizh Salsabila Pradana; Ilyas Nuryasin; Aminudin Aminudin (Ikatan Ahli Informatika Indonesia (IAII), 2023)
Errors often occur during the requirements elicitation stage, causing failure of the software development process as a whole, so that the built system cannot be used optimally; these data are obtained from survey data from several large companies involved in technology development. To overcome this problem, this study tries to apply the elicitation requirements using the KAOS method in the case study of the SMM reseller ordering system to obtain system requirements that are in accordance with the goals and objectives of each existing stakeholder. Based on the elicitation of system requirements, functional requirements are generated that include automatic orders, automatic payments, manage product sales, manage orders, manage payment methods, manage problem orders, manage customer data, manage company information, automatic email notifications, and sales statistics information. The results of this study are a table of functional requirements that have been declared valid and in accordance with the goals and requirements of each stakeholder after evaluating and validating the results for each stakeholder involved.